La inseguridad de los periodistas en Ecuador - Barberán Rodríguez, Nelly Nicole (2023)
The following project will seek to analyze the cases of violence that journalists from TC Televisión and Diario Expreso face in terms of journalistic coverage. In chapter one the problem will be raised, as well as its justification that gives way to the writing of concrete objectives that sustain this investigation with a mixed focus: qualitative. The chapter seeks to characterize the theoretical references on security, limitation of freedom of expression and violation of human rights in the journalistic exercise accompanied by antecedents and the legal framework. In chapter three, we seek to identify the most common cases of violence faced by journalists in the media in the studio by means of surveys and interviews in order to assess the level of physical and psychological risks that media journalists experience on a daily basis. to finally propose strategies and tactics that improve safety in the journalistic exercise.